Managerial Supervision and Performance of School/Madrasah Principals in Improving Education Quality - Sari, Nori Nopita (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
Referring to Regulation of Minister of Education 12 of 2007 and Minister of Religion Regulation 2 of 2012 regulating technical managerial supervision in schools and madrasah. This study aims to introduce types of managerial supervision and look at the efforts of school and madrasa principals in carrying out good and correct performance. This study uses a qualitative method with the type of literature study that relies on bibliographic sources such as books and scientific articles that are relevant to the subject matter. The results of this study show that managerial supervision has a basic concept, namely a definitive description, basic goals, principles and techniques in improving quality referring to Regulation of Minister of Education 12 of 2007 and Minister of Religion Regulation 2 of 2012. Meanwhile, the performance of school/madrasah principals is seen from the basic objectives. the assessment must be carried out through the methods and procedures for carrying out the main functional assessment, the main functional elements and the performance index of the principal of the school/madrasah.